Implementation of Character Education through Handling Students Problems with A Scientific-Based Legal Approach Strategy at SMPN 9 Kendari - Milwan (International Journal of Management and Education in Human Development, 2021)
This work is motivated by the presence of various student behaviors enjoyed by the teacher every day, even in the classroom even when the learning process is ongoing. There are still many male students who like to disturb female students, going in and out of class, and finally manifesting in an ineffective learning process, even fights occur, students are found who take things that are not their right, suck Fox glue, abuse so that this behavior is classified into problem students. With problems; (1) What is the strategy of a scientific-based legal approach in handling problematic students in the implementation of character education at SMP Negeri 9 Kendari; (2) How are the positive attitudes and behaviors of SMP Negeri 9 Kendari students changing in their daily lives through a scientific-based legal approach strategy in dealing with problematic students. The purpose of this work is to find out: (1) Knowing the strategy of a scientific-based legal approach in handling problematic students in the implementation of character education at SMP Negeri 9 Kendari; (2) Knowing the strategy of a scientific-based legal approach to students with problems so that they can increase positive attitude and behavior changes in everyday life. The results of this study are (1) Handling problematic students through a scientific-based legal approach strategy in learning all subjects can increase the percentage of attendance by 96.87%, which previously when still sitting in Class VIII Semester 2 the percentage of attendance only reached 64%. (2) it is proven that before the implementation of handling problematic students through a scientific-based legal approach strategy, student violations are very high, this is because students still do not understand in depth the impact of bad behavior, they do not even know the legal basis or sanctions if someone does something that can harm others, including the rules at school. The results of the recapitulation of student discipline violations, after the application of handling problematic students through a scientific-based legal approach strategy, it was proven that there was a significant increase in students' attitudes towards the application of discipline at school, students were diligent in coming to school on time so they could attend the morning apple, all already dressed in uniform according to the time of day that has been set by the school, it is rare for students to be late for class, really maintain the cleanliness of the school environment so that it is no longer seen that there are students throwing trash in any place, assignments or homework given by subject teachers have done at home or in groups. Handling problematic students through a scientific-based legal approach strategy is a real effort made by SMP Negeri 9 Kendari to create a creative, innovative, and fun learning atmosphere so that student learning outcomes can increase.